Ответ:
1) (x+3)² = x²+2x×3+3² = x²+6x+9
2) (4-y)² = 16-8y+y² = y²-8y+16
3) (2m-5)² = (2m)²-2×2m×5+5² = 4m²-20m+25
4) (7a+6b)² = (7a²)+2×7a×6b+(6b)² = 49a²+84ab+36b²
5) (a²-1)² = (a²)²-2a²×1+1² = a⁴-2a²+1
6) (x³-x²)² = (x³)²-2x³×x²+(x²)² = x⁶-2x⁵+x⁴
7) (-8-4c)² = 64+64c+16c² = 16c²+64c+64
8) (-x³+3)² = (3-x³)² = 9-6x³+x⁶ = x⁶-6x³+9
Объяснение:
1) (х+3)²= х²+2х•3+3²=х²+6х+9
2) (4-у)²=4²-2•4•у+у²=16-8у+у²
3) (2m-5)²=(2m)²-2•2m•5+5²=
=4m²-20m+25
4) (7a+6b)²=(7a)²+2•7a•6b+(6b)²=
=49a²+84ab+36b²
5) (a²-1)²= (a²)²-2a²•1+1²=a⁴-2a²+1
6) (x³-x²)²=(x³)²-2x³x²+(x²)²=
=x⁶-2x⁵+x⁴
7) (-8-4c)²=(-8)²-2•(-8)•4c+(4c)²=
=64+64c+16c²
8) (-x³+3)²=(-x³)²+2•(-x³)•3+3²=
=x⁶-6x³+9
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1) (x+3)² = x²+2x×3+3² = x²+6x+9
2) (4-y)² = 16-8y+y² = y²-8y+16
3) (2m-5)² = (2m)²-2×2m×5+5² = 4m²-20m+25
4) (7a+6b)² = (7a²)+2×7a×6b+(6b)² = 49a²+84ab+36b²
5) (a²-1)² = (a²)²-2a²×1+1² = a⁴-2a²+1
6) (x³-x²)² = (x³)²-2x³×x²+(x²)² = x⁶-2x⁵+x⁴
7) (-8-4c)² = 64+64c+16c² = 16c²+64c+64
8) (-x³+3)² = (3-x³)² = 9-6x³+x⁶ = x⁶-6x³+9
Verified answer
Объяснение:
1) (х+3)²= х²+2х•3+3²=х²+6х+9
2) (4-у)²=4²-2•4•у+у²=16-8у+у²
3) (2m-5)²=(2m)²-2•2m•5+5²=
=4m²-20m+25
4) (7a+6b)²=(7a)²+2•7a•6b+(6b)²=
=49a²+84ab+36b²
5) (a²-1)²= (a²)²-2a²•1+1²=a⁴-2a²+1
6) (x³-x²)²=(x³)²-2x³x²+(x²)²=
=x⁶-2x⁵+x⁴
7) (-8-4c)²=(-8)²-2•(-8)•4c+(4c)²=
=64+64c+16c²
8) (-x³+3)²=(-x³)²+2•(-x³)•3+3²=
=x⁶-6x³+9